Screening and Characterization of Putative Amylase Gene Isolated from Bacillus licheniformis P7 - Nadhirah Aminah, Binti Azizan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Amylase is one of the essential enzymes that break down starch and glycogen and it is consist of alpha-amylase and beta-amylase. It is one of the crucial enzymes that is widely used in industry. It responsible in degrading alpha 1-4 glucosidic linkages of starch and related substrates in an endo-fashion producing oligosaccharides including maltose, glucose and alpha limit dextrin. The isolation of the amylase gene is fundamental steps before cloning and characterizing of the gene take place. The amylase gene can be isolated from many microorganisms. However, the most commonly used for the industrial production are Bacillus licheniformis, Bacillus subtilis, Bacillus amyloliquifaciens and Aspergillus niger. The characterization of the amylase gene allows the understanding of expression level of amylase gene through the production of amylase enzyme in different parameters such as effect of pH, temperature and metal ions on enzyme activity. In this research study, the amylase gene is isolated from Bacillus licheniformis P7. The bacteria was also screened for amylase production. The amylase gene is detected using primers that specifically targeting the amylase gene with expected size 900 bp. The experiment was continued with molecular cloning, transformation followed by characterization of the isolated amylase gene. However, the plasmid was failed to be extracted and was troubleshoot in the discussion. Consequence to that, characterization of the amylase gene were also failed to be performed and the isolate was sent for direct sequencing.